2022
DOI: 10.1038/s41598-022-24663-y
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional SiC/AlN based type-II van der Waals heterobilayer as a promising photocatalyst for overall water disassociation

Abstract: Two-dimensional (2D) van der Waals (vdW) heterostructures made by vertical assembling of two different layers have drawn immense attention in the photocatalytic water disassociation process. Herein, we suggest a novel 2D/2D vdW heterobilayer consisting of silicon carbide (SiC) and aluminum nitride (AlN) as an exciting photocatalyst for solar-to-hydrogen conversion reactions using first-principles calculations. Notably, the heterostructure presents an inherent type-II band orientation wherein the photogenic hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…The optimized lattice constants of monolayers AlN, GaN, InN, SiC, GeC, and SnC are 3.13, 3.19, 3.62, 3.10, 3.25, and 3.61 Å, respectively, which are consistent with the values reported in the literature. 57–63 Herein, we construct a 5 × 5 supercell as the base (Fig. 1, middle column) to absorb intermediates and found that H*, O*, and HO* intermediates tend to absorb at the T1 site of AlN, InN, and SnC, while for SiC : O* at T1, H* and HO* on T2; for GeC : HO* on T2, H* and O* on T1; for GaN : H* on T2, O* and HO* on T1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimized lattice constants of monolayers AlN, GaN, InN, SiC, GeC, and SnC are 3.13, 3.19, 3.62, 3.10, 3.25, and 3.61 Å, respectively, which are consistent with the values reported in the literature. 57–63 Herein, we construct a 5 × 5 supercell as the base (Fig. 1, middle column) to absorb intermediates and found that H*, O*, and HO* intermediates tend to absorb at the T1 site of AlN, InN, and SnC, while for SiC : O* at T1, H* and HO* on T2; for GeC : HO* on T2, H* and O* on T1; for GaN : H* on T2, O* and HO* on T1.…”
Section: Resultsmentioning
confidence: 99%
“…The optimized lattice constants of monolayers AlN, GaN, InN, SiC, GeC, and SnC are 3.13, 3.19, 3.62, 3.10, 3.25, and 3.61 Å, respectively, which are consistent with the values reported in the literature. [57][58][59][60][61][62][63] Herein, we construct a 5 × 5 supercell as the base (Fig. Identifying the catalytic sites forms the cornerstone of unearthing the reaction reactivity.…”
Section: Catalyst Surface and Surface Pourbaix Analysismentioning
confidence: 99%
“…In the last decade, several scientific breakthroughs have been made in two-dimensional (2D) materials, 1–5 including graphene, 6–19 hexagonal boron nitride ( h -BN), 20–48 transition-metal dichalcogenides (TMDCs), 49–66 layered double hydroxides (LDHs), 67–74 metal–organic frameworks (MOFs), 75–79 black phosphorus (BP), 80–87 and so many others. 88–116 In particular, 2D h -BN, a geometrical analogue to graphene, is extensively studied due to its distinctive chemical and physical features. Despite the possibility that the lattice characteristics of h -BN are identical to those of carbon, the distinct constituent components give it highly diverse physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, applying strain on heterostructures has been a commonly used method for manipu-lating their optoelectronic characteristics. Prior studies have established that strain engineering can induce changes in the bandgap, [53][54][55] relocation of the band edge, 56 enhancement of the optical absorption coefficient, [57][58][59] and ad-justment of the band alignment of the hetero-structures. 60 To gain a complete understanding of the geometry, electronic and optical properties of AgBr/SiH vdW heterojunctions and how these properties are affected by strain, further research is needed as the current knowledge on this topic is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, applying strain on heterostructures has been a commonly used method for manipu-lating their optoelectronic characteristics. Prior studies have established that strain engineering can induce changes in the bandgap, 53–55 relocation of the band edge, 56 enhancement of the optical absorption coefficient, 57–59 and ad-justment of the band alignment of the hetero-structures. 60…”
Section: Introductionmentioning
confidence: 99%